A Comprehensive Stylistic Examination of the Lyrics of Let It Be by The Beatles - Putra Lamantara (PRAGMATICA : Journal of Linguistics and Literature, 2025)
This study conducts a stylistic analysis of the lyrics of The Beatles’ “Let It Be,” focusing on its linguistic features, rhetorical devices, and thematic construction. Drawing on insights from scholars such as Alan W. Pollack, Susan Fast, and Mark Spicer, the research employs a qualitative textual analysis within a stylistic framework to examine lexical choices, syntactic patterns, figurative language, and sound devices. The findings demonstrate how these stylistic elements contribute to the song’s communicative function and emotional resonance, positioning “Let It Be” as a culturally enduring text with significant artistic and linguistic value.